AhNPR3 regulates the expression of WRKY and PR genes, and mediates the immune response of the peanut (Arachis hypogaea L.). (24th March 2022) - Han, Suoyi; Zhou, Ximeng; Shi, Lei; Zhang, Huayang; Geng, Yun; Fang, Yuanjin; Xia, Han; Liu, Hua; Li, Pengcheng; Zhao, Shuzhen; Miao, Lijuan; Hou, Lei; et al.
SUMMARY: Systemic acquired resistance is an essential immune response that triggers a broad‐spectrum disease resistance throughout the plant. In the present study, we identified a peanut lesion mimic mutant m14 derived from an ethyl methane sulfonate‐mutagenized mutant pool of peanut cultivar "Yuanza9102." Brown lesions were observed in the leaves of an m14 mutant from seedling stage to maturity. Using MutMap together with bulked segregation RNA analysis approaches, a G‐to‐A point mutation was identified in the exon region of candidate gene Arahy.R60CUW, which is the homolog of AtNPR3 (Nonexpresser of PR genes) in Arabidopsis. This point mutation caused a transition from Gly to Arg within the C‐terminal transactivation domain of AhNPR3A. The mutation of AhNPR3A showed no effect in the induction of PR genes when treated with salicylic acid. Instead, the mutation resulted in upregulation of WRKY genes and several PR genes, including pathogenesis‐related thaumatin‐ and chitinase‐encoding genes, which is consistent with the resistant phenotype of m14 to leaf spot disease . Further study on the AhNPR3A gene will provide valuable insights into understanding the molecular mechanism of systemic acquired resistance in peanut. Moreover, our results indicated that a combination of MutMap and bulked segregation RNA analysis is an effective method for identifying genes from peanut mutants. Significance Statement: Peanut is one of the most important oil crops in the world. In the present study, we identified a peanut lesion mimic mutant m14 and found that a G‐to‐A point mutation in the exon region of candidate gene AhNPR3A . The mutant site contributed to the lesion mimic phenotype of m14, and is related to the systemic acquired resistance of the peanut plant. AhNPR3A is valuable for improving the resistance of peanut and further understanding of the molecular mechanism of systemic acquired resistance in peanut.